Minimum Service Standards for Basic Education in Border Region - Samion Samion; Yudi Darma Darma (JETL (Journal of Education, Teaching and Learning), 2018)
This study aims to analyze the achievement of MSS Basic Education, with a case study in the border area Entikong District of the district, followed by alternatives for achieving the standards in 2017 and prepare a strategy for its achievement. The method used in the study is the evaluation of research with the evaluation model inaccuracies or gaps (The Discrepancy Evaluation Model). This research subject is the Education Unit at the District Cabdikpora environment Entikong Sanggau consisting of principals and teachers, and Head Cabdikpora. The data used are primary and secondary data. The findings of these studies it is known that the availability of educational unit within an affordable than permanent settlement group; the number of students in each group learning for SD/MI does not exceed 32 people, while SMP/MTs exceeding 36, not available 1 (one) classrooms and there are not furnished with a table and chairs; each SMP/MTs provided a laboratory space science; Each Primary School/not available 1 (one) class teachers for each study group and for SMP/MTs unavailable teacher of Religious Education, Indonesian, Social Sciences, Arts, PE, and ICT; each SD/MI and SMP/MTs provided two (2) teachers who meet the academic qualifications S1 as much as 70%, but does not have a teaching certificate for the SD/MI; Chief of SD/MI has not qualified academic S-1 or D-IV and have a teaching certificate, already for SMP/MTs; curriculum development and innovative learning process is not implemented effectively; 50% SD/MI which has 100 titles enrichment and 10 reference books and each SMP/MTs 200 items of enrichment books and 20 reference books; 58.33% of permanent teachers work 35 hours per week in the education unit; 66.66% educational unit organized a learning process for 34 weeks per year; 66.66% The principal supervising lessons and provide feedback to teachers twice each semester.